Long-term thermal power planning at VEW ENERGIE using a multi-interval Bloom and Gallant method. - Nabona, N. (IEEE Transactions on power systems)
Bloom and Gallant have proposed an elegant model for finding the optimal thermal schedule subject to matching the load duration curve and general linear constraints. Their method is based on a linear program with some linear equality constraints and many linear inequality constraints. There are well-documented specialized linear programming algorithms that are able to solve this problem. This paper proposes the extension of the Bloom and Gallant model to several successive intervals with constraints on generation encompassing different intervals. A procedure for finding an initial feasible point, which is an essential part of the solution procedure, is described here, together with details of the modeling of several operational constraints and computational results with real test cases